METACOGNITIVE STRATEGY: How the Students Perceive the Use of Metacognitive Strategy on Their Reading Performance - Dian Resty Pratiwi (Universitas Sembilanbelas November Kolaka, 2016)
Metacognitive strategy is one of learning strategies which leads students to be proficient readers. This study aimed to investigate (1) students’ perception toward metacognitive strategy on their reading performance. This study employed qualitative research design which involves 19 undergraduates of Lakidende University Kendari. To gain the data, interview and students’ self-diary were used. Both the result of students’ self-diary and interview were positive. This study concluded that the students supported the use of metacognitive strategy on their reading performance.